EVALUASI PENERAPAN REKAM MEDIS ELEKTRONIK PADA FASILITAS PELAYANAN KESEHATAN DI INDONESIA: A SYSTEMATIC REVIEW - Rahayu, Eka Putri; Ariyanti, Rea (Departemen of Health Policy and Management, Faculty of Medicine, Public Health, and Nursing, Universitas Gadjah Mada, Yogyakarta Jl. Farmako Sekip Utara Yogyakarta 55281 Telp 0274-547490, 2025)
Background: The issuance of the Minister of Health Regulation Number 24 of 2022 requires every health care facility to improve the medical record management system that has not been implemented optimally. Every health care facility, including hospitals, is required to implement an electronic patient medical history recording system no later than December 2023. With the implementation deadline ending at the end of 2023, many health care facilities are immediately complying with the regulation, although in reality not all health care facilities have been able to implement Electronic Medical Records according to its standards. Objectives: This study aims to evaluate the implementation of electronic medical records in health care facilities in Indonesia. Methods: This study is a systematic review compiled based on the PRISMA flowchart method as a guide. Three electronic databases used in the literature search are: Portal Garuda, Pubmed and Science Direct. Boolean